Analysis of Human Resource Management in Improving Employee Performance in the Workplace - Feriandy (Indonesian Journal of Business Analytics, 2025)
This study aims to analyze the role of human resource management (HRM) in improving employee performance in the workplace. In an era of increasingly tight business competition, effective HR management is the main key for organizations to achieve competitive advantage through increasing employee productivity and work quality. The study uses a qualitative approach with a literature method. review , which examines various theories, concepts, and previous research results related to HR practices, employee development, organizational culture, leadership, and reward systems that affect performance. The results of the analysis indicate that strategic HR management, including proper planning, ongoing training, performance evaluation, and a supportive organizational culture, inspiring leadership, and a fair reward system, significantly increase employee motivation, loyalty, and productivity. This study provides theoretical and practical contributions for organizations in designing holistic HR policies to improve performance sustainably.